Research status and prospect of vacuum degree detection methods for vacuum circuit breaker - WU Mengze; SONG Jiancheng; GAO Yunguang; CHEN Shushu (Gong-kuang zidonghua, 2018)
Research status of vacuum degree detection methods for vacuum circuit breaker was introduced including off-line detection methods such as observation method, power frequency withstand voltage method, pulsed magnetron discharge method and shield potential method, and on-line detection methods such as coupling capacitance method, partial discharge method, rotary electric field probe method, X ray method and built-in sensor method. Though analyzing detection principle, characteristics and application of each method, it indicated that pulsed magnetron discharge method and power frequency withstand voltage method in off-line detection methods were the most widely applied because of low cost, simple detection and good repeatability, but regular stopping to check vacuum degree became the most important factor to restrict development of the off-line detection methods, and on-line detection methods could detect vacuum degree in real time and find deterioration of vacuum degree, but the methods were not widely applied because of low accuracy, high cost and poor anti-interference and stability. Development trends of vacuum degree detection method for vacuum circuit breaker were proposed, which were improving accuracy of on-line vacuum degree detection method and integrating multiple vacuum degree detection methods.